Socialization of Training and Utilization of Organic Waste with the Eco Enzyme Concept as a Multifunctional Liquid in Temiyang Village, Kroya District, Indramayu Regency - Didik Himmawan; Tina Sholikha (Kawakib: Journal of Multidisciplinary Research, 2025)
Lack of public knowledge regarding the use of organic waste. Through training outreach and the use of organic waste with the concept of eco enzymes as multifunctional liquids, it can help the people of Temiyang Village to develop activities for utilizing organic waste in their daily lives. The method used is a qualitative method, namely conducting observations and interviews which are followed up with socialization and training methods. The method for collecting data for this activity is by using a pre-test and post-test, which is then analyzed using the N-Gain Test to determine the category or level of understanding of the audience towards the socialization material provided.